Lessons Learned from Social Forestry Policy in Java Forest: Shaping the Way Forward for New Forest Status in ex-Perhutani Forest Area - Andita Aulia Pratama (Jurnal Ilmu Kehutanan)
Forest resource control in Indonesia has progressed from stringent state control towards a more community and indigenous based. Indonesia has embarked a journey in agrarian reform and social forestry to achieve a more balanced portion of forest resource control. The social forestry has manifested in the Collaborative Forest Management Program (PHBM) by Perhutani with the establishment of Forest Community Institution (LMDH) as its core. Forest for Special Purpose (KHDTK) Getas – Ngandong was chosen as the study case since it offers striking issue in social forestry program in the past and the outlook for the new forest status. This paper attempted to identify the policy learning from the past forest resource arrangement i.e., social forestry policy for the new forest status outlook. We identified the policy prior to the social forestry program and the implementation of social forestry from Perhutani. Subsequently, we identified policy learning from that past policy and tried to formulate the policy outlook for the new forest status. The data obtained through an interview to key informants complemented with observation, study literature, and document study. We found that past policy does not incorporate the local community in the forest utilization. The social forestry by Perhutani in their PHBM also showed indifferent approach which positioned the local community unequal with the Perhutani as social forestry promised. We identified fundamental changes should be done, which should prioritize social aspect before seeking out the economic and ecological restoration of the forest. We found the new forest status might hamper the implementation for the new forest policy which driven by the social forestry ideas. If only the new forest status could enable social aspect, the new manager will require tremendous support, robust institution, and plentiful resources to implement their policy.